1998
DOI: 10.1177/088391159801300302
|View full text |Cite
|
Sign up to set email alerts
|

Bioartificial Polymeric Material: Poly(Ethylene Glycol) Crosslinked with Albumin. II: Mechanical and Thermal Properties

Abstract: A family of hydrogels based on the crosslinking of bovine serum albumin (BSA) and activated poly(ethylene glycol) (PEG), were characterized. The swelling process was found to be dependent on the molecular weight of the PEG used and on the OH/NH2 molar ratio of the reagents. These hydrogels performed a volume expansion from 266 to 554% when PEG with molecular weights from 3,350 to 20,000 were used. The volume expansion was greater when the OH/NH2 molar ratio increased. Some anisotropy occurred during swelling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The details of the hydrogel synthesis have been published elsewhere. 2,[18][19][20][21] In brief, hydrogel formation is achieved via a condensation reaction between the amino groups of protein and carbonate-activated PEG with subsequent release of p-nitrophenol molecules. As a result of this reaction, stable urethane linkages between a biopolymer and PEG are formed.…”
Section: Synthesis Of Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the hydrogel synthesis have been published elsewhere. 2,[18][19][20][21] In brief, hydrogel formation is achieved via a condensation reaction between the amino groups of protein and carbonate-activated PEG with subsequent release of p-nitrophenol molecules. As a result of this reaction, stable urethane linkages between a biopolymer and PEG are formed.…”
Section: Synthesis Of Hydrogelsmentioning
confidence: 99%
“…2 The protein component of the hydrogel contributes to the ''tissue-like'' properties, whereas the bioinert polymer chains of PEG are responsible for the hydrophilicity of the material. This hydrogel contains up to 96% of water 2,18,19 and is presently used as a moist wound dressing and transdermal drug delivery device. Recent studies demonstrated that the PEG-protein hydrogel is inflammatory inert and accelerates wound closure in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels, three-dimensional networks of hydrophilic polymer chains, have found many applications in biomedicine and biotechnology due to their high water content, soft tissue-like consistency, and, thus, potential biocompatibility. They have been used in such areas as tissue engineering, artificial organs, and drug release devices. , Poly( N -alkyl acrylamides), pNIPAm, in particular, have been extensively studied with respect to their thermoresponsivity. , These systems undergo a reversible volume phase transition (VPT) at a lower critical solution temperature (LCST) where the hydrogel hydrophobically collapses upon itself, thereby expelling water in an entropically favored fashion. Isopropyl groups in the pNIPAm side chains play an important role in this temperature-dependent phase separation above the LCST. , The temperature at which this coil-to-globule transition occurs is approximately 31 °C, , with this temperature being dependent on the identity of the N -alkyl group.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels, three-dimensional networks of hydrophilic polymer chains, have found many applications in biomedicine and biotechnology due to their high water content, soft tissue-like consistency, and, thus, potential biocompatibility. [1][2][3][4][5][6][7] They have been used in such areas as tissue engineering, artificial organs, and drug release devices. 2,7 Poly(N-alkyl acrylamides), pNIPAm, in particular, have been extensively studied with respect to their thermoresponsivity.…”
Section: Introductionmentioning
confidence: 99%
“…The shape of this peak also shows the presence of a shoulder, that may be because of the slow rate of evaporation of residual bound water that may have been present in the sample. 96 Thus overall, the materials obtained are partly crystalline. A high degree of crystallinity is not displayed most likely due to the cross-links formed with protein bound nanotubes.…”
Section: Thermal Analysesmentioning
confidence: 98%